2018
DOI: 10.3390/molecules23040892
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Photosensitizer Targeting Using Meso-Tetra(Carboxyphenyl) Porphyrin

Abstract: Mesotetra(4-carboxyphenyl)porphyrin (mTCPP) is a commercially available small molecule fluorophore and photosensitizer with four free carboxylic acid groups. mTCPP can readily be conjugated with amines for facile attachment of functional groups. In this work, we synthesized and assessed tetravalent, lysine-conjugated mTCPP, for its potential applications in targeted imaging and photodynamic therapy. Fmoc-protected d-lysine or l-lysine was conjugated to mTCPP via amide coupling with the epsilon amine group of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…The choice of optimal combinations of photosensitizers, light sources, and treatment parameters are crucial for effective PDT [42,43]. The type of photosensitizer used, oxygen concentration within target tumor cells, a dose of light applied, and concentration of photosensitizer uptaken by cancer cells determine the cancer treatment efficacy of PDT [44][45][46][47]. PDT components can directly induce cellular damage to organelles and cell membranes, depending on where they are generated [21,22].…”
Section: Basic Concept and Mechanisms Of Pdtmentioning
confidence: 99%
“…The choice of optimal combinations of photosensitizers, light sources, and treatment parameters are crucial for effective PDT [42,43]. The type of photosensitizer used, oxygen concentration within target tumor cells, a dose of light applied, and concentration of photosensitizer uptaken by cancer cells determine the cancer treatment efficacy of PDT [44][45][46][47]. PDT components can directly induce cellular damage to organelles and cell membranes, depending on where they are generated [21,22].…”
Section: Basic Concept and Mechanisms Of Pdtmentioning
confidence: 99%
“…Chitgupi and colleagues synthesized l -lysine modified with meso -tetra­(4-carboxyphenyl)­porphyrin, specifically internalized by U87 cells and without substantial phototoxicty. The derivative may be used in direct labeling of molecules or even fused with primary amino acid chain of protein, which allows synthesis of controlled targeted molecular probes . Pandey and coauthors reported on simple, fast, and stable system based on PLA and PLA-alginate particles loaded with NIR fluorophore–PtP for oxygen and glucose monitoring in patients.…”
Section: Visualizationmentioning
confidence: 99%
“…Известно, что порфирины могут использоваться как активные фотоагенты в различных оптических технологиях, в частности, в качестве фотосенсибилизаторов для целей фотодинамической терапии (ФДТ). В этой связи особое внимание привлекают порфирины с гидрофильными боковыми группами, так как они имеют высокую растворимость в водных растворах [1,2]. Однако молекулы порфиринов благодаря наличию заряженных групп в зависимости от окружения способны к различным реакциям агрегации, образованию димеров, олигомеров и т. д.…”
Section: Introductionunclassified